The Metabolic Landscape of Thymic T Cell Development In Vivo and In Vitro - Sun, Victoria; Sharpley, Mark; Kaczor-Urbanowicz, Karolina E.; Chang, Patrick; Montel-Hagen, Amélie; Lopez, Shawn; Zampieri, Alexandre; Zhu, Yuhua; de Barros, Stéphanie C.; Parekh, Chintan; Casero, David; Banerjee, Utpal; et al. (Frontiers in Immunology, 2021)
Although metabolic pathways have been shown to control differentiation and activation in peripheral T cells, metabolic studies on thymic T cell development are still lacking, especially in human tissue. In this study, we use transcriptomics and extracellular flux analyses to investigate the metabolic profiles of primary thymic and in vitro-derived mouse and human thymocytes. Core metabolic pathways, specifically glycolysis and oxidative phosphorylation, undergo dramatic changes between the double-negative (DN), double-positive (DP), and mature single-positive (SP) stages in murine and human thymus. Remarkably, despite the absence of the complex multicellular thymic microenvironment, in vitro murine and human T cell development recapitulated the coordinated decrease in glycolytic and oxidative phosphorylation activity between the DN and DP stages seen in primary thymus. Moreover, by inducing in vitro T cell differentiation from Rag1-/- mouse bone marrow, we show that reduced metabolic activity at the DP stage is independent of TCR rearrangement. Thus, our findings suggest that highly conserved metabolic transitions are critical for thymic T cell development.